Acute pancreatitis induced by mycophenolate mofetil in a kidney transplant patient - Einollahi Behzad; Dolatimehr Fardin (Society of Diabetic Nephropathy Prevention, 2015)
Acute pancreatitis is a rare life-threatening complication in patients after kidney transplantation. Here we described a 56-year-old man who had received a living related kidney transplant for an end-stage renal disease. In his regular follow-up, his serum creatinine was gradually increased and he underwent an allograft biopsy, which revealed an interstitial nephritis/tubular atrophy grade II. Mycophenolate mofetil (MMF) was prescribed to control chronic allograft nephropathy. He presented with complaints of severe abdominal pain, vomiting, loss of appetite and fever requiring hospital admission twelve days later. Acute pancreatitis was diagnosed on the basis of laboratory data and imaging findings during hospital admission. There was no history of alcohol consumption in our patient. Unfortunately he died one week later and autopsy findings demonstrated acute necrotizing pancreatitis. The bladder drainage of this patients was normal. Laboratory findings in this patient did not endorse infections and other possibilities regarding the etiology of acute pancreatitis in this patient. Therefore, we concluded that acute pancreatitis in near the patient was induced by drugs and basis on our evidence, MMF is the most important suspect. This study suggests that acute pancreatitis can be considered as a side effect of MMF.